Overexpressed lncRNA ROR Promotes the Biological Characteristics of ox-LDL-Induced HUVECs via the let-7b-5p/HOXA1 Axis in Atherosclerosis - Yu, Cong; Wu, Bin; Jiang, Jinsong; Yang, Guangwei; Weng, Chao; Cai, Fei (Frontiers in Cardiovascular Medicine, 2021)
Long non-coding RNA regulator of reprogramming (lncRNA ROR) is involved in atherosclerosis (AS), but the specific mechanism remains unclear. Expressions of lncRNA ROR, let-7b-5p, Homeobox A1 (HOXA1) and apoptosis-associated proteins in the serum of AS patients and human umbilical vein endothelial cells (HUVECs) were determined by quantitative real-time PCR (qRT-PCR) and Western blot. The relationships of lncRNA ROR, let-7b-5p and HOXA1 were analyzed by Pearson’s correlation test. The viability and migration of HUVECs were measured by Cell Counting Kit-8, wound-healing and Transwell assays. The predicted target gene and potential binding sites were confirmed by dual-luciferase reporter assay. LncRNA ROR was highly expressed in AS, which promoted cell viability migration and invasion of HUVECs, while LncRNA ROR silencing produced the opposite results. Let-7b-5p, which bound to lncRNA ROR, its expression was down-regulated in AS, indicating that the two genes were negatively correlated. Besides, let-7b-5p reversed the effects of up-regulated lncRNA ROR expression on let-7b-5p expression, cell viability and migration as well as the expressions of apoptosis-related proteins of ox-LDL-treated HUVECs. HOXA1 was targeted by let-7b-5p and up-regulated in AS, with its expression being negatively correlated with let-7b-5p but positively correlated with lncRNA ROR. In ox-LDL-treated HUVECs, overexpressed HOXA1 reversed the effects of let-7b-5p, and HOXA1 silencing reversed the effects of lncRNA ROR. In AS, lncRNA ROR promoted biological characteristics of oxidation of low-density lipoprotein-induced (ox-LDL-induced) HUVECs via let-7b-5p/HOXA1 axis.